Assessment of Total Phenolic, Flavonoid Content and Antioxidant Activity of Ocimum sanctum Linn - Pathak, Ishwor; Niraula, Muna (Journal of Nepal Chemical Society, 2019)
Ocimum sanctum, commonly known as Tulasi in Nepal, is a pharmacologically important plant due to its active constituents. In this work, extraction was carried out in hexane, chloroform and methanol solvents and their phytochemical screening was performed. Total phenolic and flavonoid contents in the plant were measured by Folin-Ciocalteu colorimetric method and aluminum chloride colorimetric method respectively. Antioxidant activity of the extracts was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. Alkaloids, flavonoids, tannins, glycosides, polyphenols, terpenoids, tannins and steroids are mainly found in the extracts. Based on the result obtained, the plant posses a significant amount of total phenolic and total flavonoid content. Both phenolic and flavonoid contents were highest in methanol extract, followed by chloroform and hexane extract. Antioxidant activity of the extracts as ascorbic acid standard (IC50 value = 41.34 µg/mL) was in the order of methanol extract (IC50 value = 47.73 µg/mL) > chloroform extract (IC50 value = 79.46 µg/mL) > hexane extract (IC50 value = 94.68 µg/mL). The extent of the antioxidant activity of the plant is following the number of total phenolics and flavonoids present in it.